The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1017/nws.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

The perception of status: How we infer the status of others from their social relationships

Abstract: This paper investigates how we infer the status of others from their social relationships. In a series of experimental studies, we test the effects of a social relationship's type and direction on the status judgments of others. We demonstrate empirically, possibly for the first time, a widely-assumed connection between network structure and perceptions of status; that is, that observers do infer the status positions of group members from their relationships. Moreover, we find that observers' status judgments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This choice of the level of analysis makes it impossible to look at the finer-grained dyadic and triadic patterns required for understanding the interplay between bullying and peer status. Whereas such studies on social relationships and status have recently started emerging (Betancourt, Kovács, & Otner, 2018, for bullying and related behaviors see Appendix B), the specific puzzle of how bullying and status attribution affect one another has so far remained unaddressed. To address this puzzle, we put forward what might be termed a network understanding of the mechanisms that allow high-status bullies to keep their high status while staying bullies, even when bullying is disapproved of.…”
Section: The Way Bullying Work: How New Ties Facilitate the Mutual Reinforcement Of Status And Bullying In Elementary Schoolsmentioning
confidence: 99%
“…This choice of the level of analysis makes it impossible to look at the finer-grained dyadic and triadic patterns required for understanding the interplay between bullying and peer status. Whereas such studies on social relationships and status have recently started emerging (Betancourt, Kovács, & Otner, 2018, for bullying and related behaviors see Appendix B), the specific puzzle of how bullying and status attribution affect one another has so far remained unaddressed. To address this puzzle, we put forward what might be termed a network understanding of the mechanisms that allow high-status bullies to keep their high status while staying bullies, even when bullying is disapproved of.…”
Section: The Way Bullying Work: How New Ties Facilitate the Mutual Reinforcement Of Status And Bullying In Elementary Schoolsmentioning
confidence: 99%
“…She found effects for referrers (current employees who recommend new hires to their boss), but other studies have found little to no effect of references listed in job applicants' resumes (Pager 2003). This, along with social network experiments (Betancourt, Kova ´cs, and Otner 2018), illustrates that how actors are connected, and the experiences on which relationships are based, is theoretically and practically crucial for determining whether status will spread by association. The present studies illustrated that status-valued task relationships grounded in relevant experience produce behavioral inequalities in novel situations.…”
Section: Discussionmentioning
confidence: 92%
“…Network position is appropriate for capturing an individual’s status, because those who are the most central in the social network of an organization are typically those thought to be the most competent employees or star performers (Ibarra, 1993; Kehoe et al, 2016; Oettl, 2012; Oldroyd and Morris, 2012). Indeed, Betancourt et al (2018) showed that individuals ascribed the most status to members of a social network who were the most central in three different types of network. In addition, our industry experts noted that they themselves used network centrality as a measure of status, as one of them explained:
‘Social networks are very important in this industry […] and they can be very valuable.
…”
Section: Methodsmentioning
confidence: 99%